An investigation into the partial oxidation of C-4 alkanes over vanadyl pyrophosphate and heteropoly acids - Robertson, Stéfan Walters (Department of Chemical Engineering, 2023)
Two different partial oxidation catalysts for paraffin functionalisation were studied: the vanadyl pyrophosphate catalyst for the conversion of n-butane to maleic anhydride and the heteropoly acid catalyst for the conversion of isobutane to methacrylic acid.